A Case-Study of a Child with Reversible Posterior Leukoencephalopathy Syndrome (RPLS) Associated with Severe Burns throughout the Body - Koji WAKE; George IMATAKA; Toshihiko OHNISHI; Jin KIKUCHI; Eisei HOSHIYAMA; Kazuyuki ONO; Shigemi YOSHIHARA (Tehran University of Medical Sciences, 2020)
N A